MOLAR-INCISOR HYPOMINERALIZATION (MIH): FROM DIAGNOSIS TO TREATMENT - A SYSTEMATIC REVIEW - Caroline Ribeiro Lacerda, Anne; Durando Rebouças, Beatriz; Cirqueira Araujo Telles Nouzinho, Clarisse; Alves Freitas Cruz, Kádja; Cavalcante Carneiro, Laís; Jordania Lino Figueredo, Lívia; de Souza Pereira, Malvina; da Silva Oliveira, Thaís (Health and Society, 2024)
Introduction: Irregular tooth enamel on one or more molars or even permanent incisors is Incisor Molar Hypomineralization (IMH), a condition that directly affects the experience of the affected person. Objective: This systematic review aims to list the specificities of MIH based on the aim of determining its causes and origins so that it can be understood and treated. Methodology: The databases used were: National Center for Biotechnology Information, U.S. National Library of Medicine (Pubmed), Virtual Health Library (VHL) and Scientific Electronic Library Online (Scielo), in English, Spanish and Portuguese. Totaling 1,680 articles. Of which 1,592 articles were excluded where they did not meet the inclusion criteria, resulting in 88 articles, after a complete reading, 45 articles were selected to compose the study. Results: Treatment modalities for teeth affected by MIH varied widely, depending on the severity, and the presence of complicating factors, such as hypersensitivity, oral hygiene and patient cooperation. Conclusion: MIH has an unresolved etiology with multifactorial characteristics, such as genetic factors, pathologies during pregnancy and even pollution. Incisor molar hypomineralization has a late diagnosis associated with the unskilled knowledge of professionals regarding its manifestations.